Hemodynamic study of arteriovenous fistulas for hemodialysis access. (February 2013) - Chandra, Ankur; Mix, Doran; Varble, Nicole
Dialysis access failure and associated complications represent a major cause of morbidity in patients with renal failure. This is due to an incomplete understanding of the hemodynamics associated with both arteriovenous fistula (AVF) successes and complications. Several decades of research have been performed studying these complex hemodynamic changes. This review provides an overview of work undertaken in three key areas of AVF hemodynamic research: mathematical modeling, in vivo fluid dynamic measurements and in vitro fluid dynamic modeling. Current and future work is then summarized involving the application of a comprehensive, systematic study of dialysis access hemodynamics. The ultimate goal is the ability to predict clinical outcomes of dialysis access procedures through personalized, patient-specific surgical planning. If successful, this type of tool would allow surgeons to predict multiple-dialysis access intervention outcomes and choose a personalized approach to maximize success.